Multiplicity Results for a Perturbed Elliptic Neumann Problem - Gabriele Bonanno; Giuseppina D'Aguì (Abstract and Applied Analysis)
The existence of three solutions for elliptic Neumann problems with a perturbed nonlinear term depending on two real parameters is investigated. Our approach is based on variational methods.